ASSESSMENT OF DEVELOPMENT TENDENCIES OF GENERAL FOOD SERVICES (Marketing Journal, 2025)
The article describes the modern methodological approaches of establishing econometric provision of food and general catering services development. In particular, a complex system of indicators for complex economic analysis of the activities of public accommodation and catering enterprises, a scenario for classifying the analysis of the activities of enterprises by criteria, and economic statistical a nalysis of development are presented.
Keywords: econometric model; hotel and catering; complex economic analysis; system of indicators; synergetic factors; analysis classification criteria